High-Performance Region-of-Interest Image Error Concealment with Hiding Technique - Shih-Chang Hsia; Szu-Hong Wang; Ming-Huei Chen (Journal of Electrical and Computer Engineering)
Recently region-of-interest (ROI) based image coding is a popular topic. Since ROI area contains much more important information for an image, it must be prevented from error decoding while suffering from channel lost or unexpected attack. This paper presents an efficient error concealment method to recover ROI information with a hiding technique. Based on the progressive transformation, the low-frequency components of ROI are encoded to disperse its information into the high-frequency bank of original image. The capability of protection is carried out with extracting the ROI coefficients from the damaged image without increasing extra information. Simulation results show that the proposed method can efficiently reconstruct the ROI image when ROI bit-stream occurs errors, and the measurement of PSNR result outperforms the conventional error concealment techniques by 2 to 5 dB.